URGENSI LITERASI BENCANA GEMPA BUMI PADA PESERTA DIDIK SEKOLAH DASAR: PERAN BUKU SAKU DAN SIMULASI MITIGASI - Frima Dewi Wulandari; Elan; Setiadi, Pidi Mohamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesia is a country with a high level of natural disaster vulnerability, especially earthquakes. Pangandaran Regency as one of the earthquake prone areas requires effective mitigation education strategies for elementary school students, which are included in vulnerable groups. This study aims to examine the importance of disaster literacy in elementary school students through the integration of educational pocket books and disaster mitigation simulations. Research used a descriptive qualitative method with a literature study approach supported by field data from 36 students at SDN 2 Karangjaladri, Pangandaran Regency. The results of the study show that disaster literacy is not sufficient to be built through the delivery of theory, but it needs to be supported by communicative learning media and contextual experience. Pocket books provide ease of access to information, facilitate independent learning, and help strengthen the understanding of mitigation concepts in a concise and attractive manner. Meanwhile, mitigation simulation provides direct learning experiences through role-play that are able to instill skills to act quickly and precisely when disasters occur. The combination of the two forms an integrative and effective learning approach, in line with the principle of an independent curriculum that emphasizes active, contextual, and participatory learning. Thus, the integration of pocket books and mitigation simulations can be a significant strategy in increasing disaster literacy of elementary school students, as well as forming a culture of preparedness early on in disaster -prone areas.